شر ح إرشاد الس اّلك المحتاج إلى بيان أفعال المعتمر والحاج للشيخ أبي عبد الله محمد بن الحسن بن مسعود بناني المغربي الفاسي المالكي ( 1194 ه) دراسة وتحقيقا. من اللوحة 15 إلى اللوحة 30 من قوله: والعمرة سنة مؤكدة مرة في العمر إلى قولهأ: ن يدخلها بحج أو عمرة - عدونة, نص الدين (جامعة الوادي university of eloued, 2017)
هذه الر سّالة هي عبارة عن تحقيق جزء شمرنح إرشاد الس اّلك المحتاج إلى بيان أفعال المعتمر والحاج ، للشيخ أبي عبد الله محمد بن الحسن بن مسعود بانُ ني المغربي الّف ا سي اّلما ل كي ( 1194 ه) دراسة وتحقيقا من الورقة 15 إلى الورقة 30 من قوله: ( ...والعمرة سنة مؤكدة مرة في العمر إلى قوله: ... أن يدخلهابح ج أو عمرة،... )وي تضم نّ هذا الجزء، أحكام العمرة لد ا ى لأئمة المالكي ةّو، شروط صح تها،وما يقوم ا من إحرامه و إلى غاية تمام نسكه، ومواقيتها الزمانية والمكانية، والأخطاء التي يقع فيها 􀄑 به الُمح رم المعتمر التي توجب الدم، والتي لا توجبه.كما تعرض الشارح إلى مو اقيت أهل مك ة الزمانية والمكانية، وإحرام أهل الآفاق والواصلين إلى مة،ك وأفضل جهات الحل ، إضافة إلى حكم إدخال الحج على العمرة، كما تطر قّ أخير ا إ لى إحرام من سافر على البحر، ومن مر بجدة . Summary This letter is a part of the explanation of the guidance of the righteous Salik to the statement of the actions of the pilgrim and the pilgrim to Sheikh Abi Abdullah Muhammad bin Hassan bin Masoud binani Moroccan Fassi al-Maliki (1194 e) study and investigation of paper 15 to paper 30 of saying: Umrah is confirmed once in the old to He said that he should enter it with Hajj or Umrah, and this part includes the provisions of the rulings on 'Umrah and the conditions of its validity, and what the Muharram does with its ihraamah, and it is very full of forgetfulness, its temporal and spatial timing, and the mistakes in which the Umrah is obligatory which requires blood, . Al-Sharh also revealed the times of the people of Mecca and the time of Makkah, and Ihram the people of horizons and the arrival to Mecca, and the best solution, adding a provision to introduce the pilgrimage to Umrah, and finally touched on Ihram who traveled on the sea, and passed through Jeddah
مذكرة
Keywords: أبي عبد الله محمد بن الحسن بن مسعود بناني-العمرة-إرشاد الساّلك المحتاج; Abi Abdullah Muhammad bin Al-Hassan bin Masoud Banani - Umrah - Guidance for the needy traveler